(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The aim of this associative, descriptive study was to measure emotional states (anxiety and depression) and assess their relationship with preoperative hospitalization lasting longer than one week. The final sample was limited to four female patients diagnosed with tumors of the nervous system who answered five open-ended questions and fourteen items on the Hospital Anxiety and Depression Scale (HADS), seven of which are used to assess anxiety (HADS-A), and seven depression (HADS-D). The final score corresponded to a state of anxiety in three patients in the sample after the questionnaire was first applied and to a state of anxiety/depression in one of the patients when the questionnaire was applied for the third time following postponement of her surgery. The hypothesis of the anxiety/depression/anxiety curve was not confirmed. The results are only considered to be valid for the study sample.